Effective data collection and analysis for efficient implement of Standardized Work (SW) / Ahmed Jaffar, Nurul Hayati Abdul Halim and Noriah Yusoff - Jaffar, Ahmed; Abdul Halim, Nurul Hayati; Yusoff, Noriah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2012)
This research paper presents an implementation of one of the Lean Manufacturing (LM) tools, known as Standardized Work (SW), at an automotive assembly line in Malaysia. The main functions of SW are to design, develop, document and visualize a set of manufacturing process with detail and proper study on it. SW is conducted to raise production efficiency and quality. Quality here referred to quality of the products to be produced and quality of the jobs to be performed. With the main objective to demonstrate a systematic and organized guideline on how data collection and analysis should be conducted with detail explanation on tools and methods used for efficient implementation of SW, a case study was conducted at an automotive components assembly line, at XYZ Manufacturing Sendirian Berhad. There are five major phases involved in the implementation of this research work; (i) observation, to understand the existing study area conditions, (ii) data collection through observation, referring to company’s production system and work study method, (iii) data analysis using SW tools, (iv) development of standardized process, and (v) results evaluation by using lean metrics to analyze the performance of the standardized assembly process. results show that, with systematic and proper implementation, SW offer a lots of benefits such as help to increase efficiency and quality and process stability in terms of productivity, quality and operator’s performance. Moreover, it also helps to achieve LM philosophies which are wastes elimination and continuous improvement during the implementation.